2022
DOI: 10.3389/fcell.2022.899869
|View full text |Cite
|
Sign up to set email alerts
|

Mesenchymal Stem Cells-Derived Exosomes Ameliorate Ischemia/Reperfusion Induced Acute Kidney Injury in a Porcine Model

Abstract: Exosomes are membrane-enclosed vesicles secreted by cells, containing a variety of biologically active ingredients including proteins, nucleic acids and lipids. In this study, we investigated the therapeutic effects of the exosomes and underlying mechanisms in a miniature pig model of ischemia/reperfusion-induced acute kidney injury (I/R-AKI). The exosomes were extracted from cultured human umbilical cord derived mesenchymal stem cells (hUC-MSCs) and infused into a miniature pig model of I/R AKI. Our results s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(19 citation statements)
references
References 61 publications
2
17
0
Order By: Relevance
“…[38] More importantly, abundant evidence has demonstrated that EVs have rare toxic effects and low immunogenicity. In line with previous reports, [21][22] we also found that xenogeneic EVs are well tolerated in vivo in this study. However, the use of xenotissue-derived EVs may still face some possible issues, such as immunologic and infectious (e.g., animal-derived viruses) effects, [39] which may be resolved by rapid progress in the gene editing system (e.g., CRISPR-Cas9) of large animals.…”
Section: Integrating Neonatal-tissue-evs With Ecm Materials For Advan...supporting
confidence: 93%
See 1 more Smart Citation
“…[38] More importantly, abundant evidence has demonstrated that EVs have rare toxic effects and low immunogenicity. In line with previous reports, [21][22] we also found that xenogeneic EVs are well tolerated in vivo in this study. However, the use of xenotissue-derived EVs may still face some possible issues, such as immunologic and infectious (e.g., animal-derived viruses) effects, [39] which may be resolved by rapid progress in the gene editing system (e.g., CRISPR-Cas9) of large animals.…”
Section: Integrating Neonatal-tissue-evs With Ecm Materials For Advan...supporting
confidence: 93%
“…[ 1b ] Importantly, many studies have reported that cross‐species EV therapies still have tissue repair roles with rare toxic or adverse effects in preclinical models. For example, human MSC‐EVs could promote renal repair and reduce inflammation in mouse [ 21 ] or porcine models [ 22 ] of ischemic AKI. For future clinical translation, xenotissues may be potential sources of tissue‐EVs since it is difficult to collect enough tissue samples from humans for therapeutic purposes.…”
Section: Resultsmentioning
confidence: 99%
“…MSCs-sEVs may also induce angiogenesis in kidney injury models, as postulated. Recent research 298 indicates that kidney-derived MSCs-sEVs promote angiogenesis in renal tissue. The therapeutic effects of sEVs, which are vesicles secreted by cells and contain various biologically active components, in a pig model of I/R-AKI was investigated.…”
Section: Applications Of Evs-loaded Hydrogels In Tissue Regenerationmentioning
confidence: 99%
“…Klotho and BMP-7 are two renoprotective proteins that are frequently downregulated in the kidney following acute and chronic injury induced by various insults. 33,34 We examined whether JMJD3 would contribute to their expression by examining the effect of GSKJ4 on their expression. As expected, I/R and FA injury caused downregulation of klotho and BMP-7; treatment with GSKJ4 further reduced their levels (Figure 7A-F).…”
Section: Inhibition Of Jmjd3 Potentiates I/r-or Fa-induced Downregula...mentioning
confidence: 99%